Direct and moderation effects on U.S. apparel manufacturers’ engagement in network ties - Nancy J. Miller; Carol Engel-Enright; David A. Brown (Journal of Entrepreneurship, Management and Innovation)
PURPOSE: Firms do not continue and prosper purely on their own individual endeavors, as each firm is influenced by the activities of others, and thus direct and indirect relationships shape the firm’s strategic management. These relationships form the tactics by which knowledge and other strategically important resources are accessed and created. Forming and maintaining ties among members of a network have been the subject of numerous research studies in the social, economic, and business literature. Our work is framed by the resource-based view of the firm perspective along with social capital theory and its shared constructs in network theory. Prior findings suggest that networking ties are strategic actions generated for firm growth and continuance. The ties may be short-term or develop into long-term relationships. The intent of this research is to fill some of the gaps in interorganizational networking strategy by analyzing five antecedents that have been suggested in the literature as individually associated with entrepreneurs’ engagement in network ties. In this way, our work provides another research avenue for examining networking’s contribution to strategic management. We hypothesized positive connections to entrepreneurs’ engagement in network ties from antecedents involving the firm’s knowledge absorptive capacity, business goals, entrepreneurial orientation, social interactions, and support from their environment. METHODOLOGY: In our quantitative approach, we tested our proposed macrolevel direct and moderating connections through an online survey of 125 U.S. apparel manufacturing firms. The apparel manufacturing sector in the U.S., as in many countries, has struggled with multiple disrupting factors contributing to the sector’s decline in firm continuance. FINDINGS: The results from OLS regression analyses support our hypothesized connections in that each of the five antecedents significantly contributed to entrepreneurs’ engagement in network ties; however, when all five were collectively examined only absorptive capacity, social interaction, and business goals were significant (R2 = 0.58). Further examination of moderation effects found the entrepreneurs’ perceptions of a supportive environment to modify both entrepreneurial orientation and business goals. RESEARCH AND PRACTICAL IMPLICATIONS: The effects of a supportive environment on business goals’ relationship with network ties were greater when perceptions of a supportive environment decreased, while the effects of a supportive environment on entrepreneurship orientation’s relationship with network ties were greater when perceptions of a supportive environment increased suggesting further study of U.S. entrepreneurs’ perceptions of their environments. Entrepreneurs’ interested in building domestic and international supply chain ties may find network ties provide one solution for adapting the firm’s resources for global competitiveness. Future studies may direct attention to other industry sectors or countries for replication with larger sample sizes as we recognize the limitations to generalizability and scale refinement due to our limited sample size. ORIGINALITY AND VALUE: The examination of five constructs to shed light on how an organization’s decisions may relate to engaging in networks and provides theoretical as well as practical implications that contribute to the larger organizational system framework.